In vitro impact of Streptococcus mitis on the inhibition of oral cancer cell proliferation via mitotic modulation - Inui, Inori; Mochizuki, Shinichi; Hirabayashi-Nishimuta, Fumika; Yoshioka, Yoshie; Takahashi, Osamu; Sasaguri, Masaaki; Habu, Manabu; Ariyoshi, Wataru; Yamasaki, Ryota (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionRecent studies have elucidated a potential correlation between oral carcinogenesis and the oral microbiome. However, few reports exist on the interaction between Streptococcus spp., the most common oral microflora bacterium, and oral cancer. In this study, we aimed to elucidate the effects of Streptococcus spp. on oral squamous cell carcinoma (OSCC) cells in vitro.MethodsHSC-3 (tongue carcinoma) and Ca9-22 (gingival carcinoma) cells were used as models of OSCC cells, and their responses were examined after adding major oral Streptococcus species—S. mitis, S. sanguinis, S. anginosus, S. salivarius, and S. mutans—to the culture medium. Cell viability was assessed using the CCK-8 assay. Gene expression changes were analyzed using RNA sequencing and RT-qPCR followed by Gene Ontology analysis. Flow cytometry was used to observe the effects of bacteria on the cell cycle.ResultsAmong all examined Streptococcus species, S. mitis had the strongest inhibitory effect on the growth of OSCC cells. RNA sequencing and RT-qPCR revealed an increase in the number of genes involved in mitotic nuclear division, especially DUSP1, in HSC-3 cells treated with S. mitis. Flow cytometry showed that S. mitis caused a decreased number of HSC-3 cells in the G0/G1 phase and an increased number in the G2/M phase, suggesting cell cycle arrest in the G2/M phase. Various treatments of S. mitis were used to examine the effects of intact bacteria and bacterial components on cancer cells, indicating the involvement of structural bacterial proteins.ConclusionsThis study, investigating the association between oral cancer cells and bacteria of the genus Streptococcus, revealed that S. mitis may play an important role in the inhibition of cancer cells.